1981
DOI: 10.1136/oem.38.4.334
|View full text |Cite
|
Sign up to set email alerts
|

Sensitisation against environmental antigens and respiratory symptoms in swine workers.

Abstract: Adverse effects caused by airborne material to the respiratory tract are due either to nonspecific irritation or to hypersensitivity. In this study 20 people employed in swine barns and 18 controls were tested for sensitisation against dusts present in the barns. Immunoprecipitation and enzyme-linked immunoassay (ELISA) were used to test for IgG antibodies; IgE antibodies against swine epithelium were tested using solid phase radioimmunoassay. Precipitins against swine antigens were found in two swine workers;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

1987
1987
1994
1994

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 5 publications
1
13
0
Order By: Relevance
“…However, 70 % of these farmers also had an elevated IgE level again st hou se du st mite (Derma tophygoides) allergens. No IgE antibodies were found again st swine ant igens; this findin g is consistent with the results of a Finnish study (4). Another study showed no difference in precip ita ting antibod ies to agents related to hypersensitivity and swine ant igens and molds isolated from the swine environment (16).…”
Section: Serologysupporting
confidence: 83%
See 3 more Smart Citations
“…However, 70 % of these farmers also had an elevated IgE level again st hou se du st mite (Derma tophygoides) allergens. No IgE antibodies were found again st swine ant igens; this findin g is consistent with the results of a Finnish study (4). Another study showed no difference in precip ita ting antibod ies to agents related to hypersensitivity and swine ant igens and molds isolated from the swine environment (16).…”
Section: Serologysupporting
confidence: 83%
“…Clinical evidence of classical hypersensitivity pneumonitis has not yet been reported (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). This lack should not, however, be interpreted as an absence of risk.…”
Section: Systemic and Other Symptomsmentioning
confidence: 99%
See 2 more Smart Citations
“…4 ardous airborn e contaminants. Previous reports show a n increased prevalenc e of respiratory ailments for both of the se environments (10,11).…”
mentioning
confidence: 99%